2015
DOI: 10.1007/s10071-015-0886-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental shifts in egg–nest contrasts do not alter egg rejection responses in an avian host–brood parasite system

Abstract: Obligate brood parasitic birds exploit their hosts to provide care for unrelated young in the nest. Potential hosts can reduce the cost of parasitism by rejecting foreign eggs from the nest. Observational, comparative, and experimental studies have concluded that most hosts use the coloration and patterning of eggshells to discriminate between own and foreign eggs in the nest. However, an alternative hypothesis is that birds use the colour contrasts between eggshells and the nest lining to identify parasitic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Consistent with this observation, hosts found to disproportionately reject brown egg models laid (at least moderately) blue-green eggs (Honza et al, 2007;Cassey et al, 2008;Soler et al, 2012;Hanley et al, 2017Hanley et al, , 2019bAbolins-Abols et al, 2019;Manna et al, 2020). Although past experiments found that nest contrast did not influence host egg recognition (Aidala et al, 2015;Hauber et al, 2015a), a blue nest lining did increase performance on an egg discrimination task by 25% in the blue-green egg laying American robin Turdus migratorius (Aidala et al, 2015). We feel this is still a promising line of research, particularly if future studies employ an experimental manipulation of nest background (Aidala et al, 2015) alongside sufficient variation in the color of egg stimuli to determine threshold values (sensu Lind, 2016).…”
Section: Perceptual Mechanismsmentioning
confidence: 58%
“…Consistent with this observation, hosts found to disproportionately reject brown egg models laid (at least moderately) blue-green eggs (Honza et al, 2007;Cassey et al, 2008;Soler et al, 2012;Hanley et al, 2017Hanley et al, , 2019bAbolins-Abols et al, 2019;Manna et al, 2020). Although past experiments found that nest contrast did not influence host egg recognition (Aidala et al, 2015;Hauber et al, 2015a), a blue nest lining did increase performance on an egg discrimination task by 25% in the blue-green egg laying American robin Turdus migratorius (Aidala et al, 2015). We feel this is still a promising line of research, particularly if future studies employ an experimental manipulation of nest background (Aidala et al, 2015) alongside sufficient variation in the color of egg stimuli to determine threshold values (sensu Lind, 2016).…”
Section: Perceptual Mechanismsmentioning
confidence: 58%
“…increasing the visual contrast between artificial parasitic eggs and the nest background did not induce egg-rejection behavior, suggesting that egg-nest contrast is not a salient visual cue in making egg-rejection decisions in this parasite-host system. Because phoebes do not respond to cowbird parasitism at the egg stage, our experimental results do not allow us to conclude a general noneffect of egg-nest visual contrast across all parasite-host systems, though recent work suggests that is likely the case (Aidala et al, 2015;Hauber et al, 2015). We caution that phoebes' lack of behavioral response to natural and artificial parasitism is a limitation of this study system because it impedes our ability to determine which, if any, variables influence parasitic egg rejection.…”
Section: Discussionmentioning
confidence: 86%
“…In our study, phoebes used neither a discordancy nor template-based rule to reject parasitic eggs (as no rejection behavior occurred). Future studies should address the cognitive bases of egg-rejection behavior (such that may exist) in nonrejecting hosts along an egg color continuum that encompasses and surpasses the natural variation of parasitic and host eggs (Aidala et al, 2015; Croston & Hauber, 2015; Hanley et al, 2017; Hauber et al, 2015). Here, we only used discrete egg colors that matched the background and maculation of phoebes’ cowbird parasites in our artificial parasitism experiments because we were specifically testing whether egg–nest visual contrast could facilitate detection of cowbird parasitism (see Method).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we suggest that the cryptic egg hypothesis is more suitable for explaining host nests that are enclosed or in dense vegetation cover with poor light conditions rather than open host nests, because dim-coloured eggs with an egg darkness or nest similarity effect are only presumed to have an effect under poor light conditions [17]. This may be one of the major reasons why some studies supported the egg darkness or nest similarity component of the cryptic egg hypothesis [13,21,24,25] while others did not [23,2628]. Although poor light conditions may favour cuckoos evolving dark eggs, egg colour mimicry is still an alternate strategy in such conditions.…”
Section: Discussionmentioning
confidence: 99%